Vaginal birth after cesarean section: Experience of four years at Uldarico Rocca Hospital, Essalud - Lindo Pérez, Misael (2015)
OBJETIVE: To determine maternal and perinatal characteristics, mode of delivery and complications of pregnant women with vaginal birth after a previous cesarean. LUGAR: Hospital Uldaric Rocca, Essalud, in 2000-2004. Mterial AND METHODS: Retrospective and descriptive study of 298 pregnant women at term with a history of a previous cesarean admitted to study for the test of labor and vaginal delivery. RESULTAOOS: The success rate of vaginal delivery was 54.7% (163 patients) with previous cesarean. 63.2% were between 26 and 35 years old. The intergenesic period from the previous cesarean and vaginal birth less than two years was 86% (14 patients). The eutócivo birth was given in 90.8% (148 patients) and vacuum was used in 9.2% (15 patients). It was stimulated with oxytocin labor in 14.7% (24 patients). The average weight of newborns (RN) was 3406g and 4.9% (8 RN) they were macrosomic. 99.4% of newborns had Apgar> = 7 at 5 minutes. There were no cases of uterine rupture. CONCLUSIONS: vaginal delivery in previous cesareada in selected group of women is considered safe and with high probability of success and minimal risk; therefore it is an acceptable alternative to avoid an elective repeat cesarean in patients with previous cesarean.